درجة التحلل الكارستي في حوض نبع السن - سلوم, جوليت (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
ينبثق نبع السنّ الكارستيّ في الصخور الكريتاسيَّة المصدّعة, على ارتفاع 11م عن سطح البحر. وهو من أهم الينابيع في حوض الساحل السوري. وما يميز حوض نبع السن غناه بالأشكال الكارستية السطحيَّة والضمنيّة كالجوبات والخدوش والآبار الكارستية, ويعزى هذا الأمر إلى الطبيعة الليثولوجية, من حيث مسامية الصخور ونفاذيتها, إضافةً إلى غنى المنطقة بالفوالق والقسمات الخطية, التي تسهل ولوج الماء داخل الصخور وأهمها الفوالق, التي تمرر مياه نبع السن. في هذه الدراسة سنحاول اختبار الأشكال الكارستية في منطقة الدراسة فيما إذا كانت تعود إلى الظروف المناخية الحالية أم أنها تعود إلى ظروف مناخية سابقة . The Sin Karastic Spring pours out from the karastic faulting rocks on 11m height above the sea level. It is one of the most important springs in the Syrian costal basin. The most essential feature of the Sin Karastic Spring Basin is its abundance with internal and external karastic forms, such as Lapiaz, Dolines and Ouvalas. This is due to the lithological nature in line with the porous and penetration rocks. This is in addition to the abundance of the study area with the joints and lineation which facilitate the entrance of water inside the rocks, especially the joints which pass the Sin Spring water. From what is stated above, this study tries to examine if the development of Karastic features in the study area relates to either the recent or the pre - climatic conditions.